(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This research examines the effectiveness of the Saung Interaktif model as a community-based environmental education strategy aimed at strengthening household waste management literacy in rural Indonesia. The initiative applied a one-group pretest–posttest quasi-experimental design involving 35 female PKK cadres from Nyalindung District, Sukabumi Regency. The intervention incorporated experiential learning components such as eco-enzyme production, composting methods, preparation of liquid organic fertilizer, environmental health education, and introductory digital marketing training. Data were gathered through a 20-item structured knowledge assessment administered before and after the program, and were analyzed using descriptive statistics along with paired comparative analysis. The results revealed a 20% increase in average knowledge scores after the intervention, reflecting meaningful gains in environmental literacy and practical waste management skills. These findings indicate that participatory, hands-on environmental education can significantly strengthen community capacity and encourage sustainable household waste practices. Nevertheless, the lack of a control group and the relatively brief monitoring period restrict the ability to draw strong causal conclusions. Overall, the Saung Interaktif model presents a scalable approach for integrating environmental education, public health promotion, and economic empowerment within rural sustainability programs.